PEMEROLEHAN LEKSIKON PADA ANAK USIA 2 TAHUN - HL, Nur Ihsan; Takwa, Takwa; Samsuddin, Samsuddin (Sunan Kalijaga State Islamic University Yogyakarta, 2021)
The forms and meanings of a 2-year-old lexicon are very interesting. The aesthetics are found in the different meanings of similar lexicon forms. The purpose of this study is to explain the forms and purpose of the lexicon of children at age 2. The method used in this research is descriptive qualitative. The subject of this research is 2-year-old children who live in the Sabilambo Village, Kolaka Regency. The object of this study is the lexicon of these children. The data collection techniques are through direct observations, recordings, notes, and interviews. The data were analyzed using a contextual approach. The context approach is used to explain the different meanings of the same lexicon forms. The results showed that the 2-year-old children during the research expressed 65 lexicons in the forms of nouns, verbs, adverbs, adjectives, and pronouns. From these lexicon forms, it is found that there are some similar forms that convey different meanings, and consequently, the understanding of a context is needed to be able to explain the meaning.